К проблеме изучения литуанизмов в периферийных польских говорах литовско-белорусского пограничья - Адомавичюте, Ирена (Kalbotyra, 1983)
This article is based on S. Bielikowicz’s work “Wiocuk gada”; the meanings and the usage of the following loan words are analysed: arbata, kul slomy, kruśnia, kulsza, lapszuk, podynka, tarpa, wiapla, wikswa, kimsy, rojsty, žergać, grabolić. It is revealed that such Polish dialect items as lenty ‘calm’ and smagle ‘merry, strong’ have originated from such Lithuanian words as lėtas and smagiai.